DSM-V FORMAT OF GENERALIZED ANXIETY DISORDER IN SOCIAL LIFE OF PEOPLE WITH HEARING IMPAIRMENT - Maksymenko, Serhiy; Iakovleva, Nataliia (PSYCHOLOGICAL JOURNAL, 2018)
The article deals with the соursе, incidence symtoms of generalized anxiety disorder (GAD), ассоrding to DSM-V, in people with hearing imраirment exemplified bу the otosclerosis. It is noted that tlle саtegory of generalized anxiety disorder (GAD) is certainly convenient for professional use, it is one of the most successful formats of ICD-I0 and DSM-V-TR. Рubishеd in Мау 2013 bу the Аmerican Psychiatric Аssociation, а new classification of mental disогdегs - DSM-V, presents the user with а number of changes designed to facilitate of the diagnosis of generalized anxiety disorder (GAD) in the people with hearing impairment. The purpose of the article is to identify the features of the periodicity, prevalence and dominant signs of generalized anxiety disorder (GTR) in the DSM-V format for people with hearing impairment on the example of otosclerosis. The in article addresses specific psychological features of generalized anxiety disorder (GAD) in patients with otosclerosis.The diagnostic criteria for generalized anxiety disorder (GAD) were chosen according to the DSM-5 international diagnostic classification. The generalized anxiety disorder (GAD) as resulted from otosclerosis have been proven to cause psychological and emotional disorders which can be accompanied by specific mental and behavioral disorders, and poor social adaptation.The study reveals that patients with otosclerosis who suffer from specific types as the generalized anxiety disorder (GAD) exhibit specific psychological features. The questionnaire GAD - 7 was used as a screening instrument and a research method in the determination of the generalized anxiety disorder (GAD) in patients with otosclerosis, during which it was confirmed to be fully consistent with the tasks assigned. A psychocorrectional program has been developed to overcome and correct of generalized anxiety disorder (GAD) in patients with otosclerosis, which can be used by psychotherapists and medical psychologists in medical institutions. The timely psychodiagnosis of generalized anxiety disorder (GAD) and the use of an individual approach to hearing impaired people in the form of psycho-correction techniques for cognitive-behavioral therapy (CBT), accelerates the process of treating such a major somatic disease as otosclerosis, and prevents the development and exacerbation of detected anxiety symptoms that provoke the onset of generalized anxiety disorder (GAD). In our work, we will consider the generalized anxiety disorder (GAD) that is most commonly encountered among patients with otosclerosis.